Comparative Analysis of Visual Performance and Optical Quality with a Rotationally Asymmetric Multifocal Intraocular Lens and an Apodized Diffractive Multifocal Intraocular Lens. (20th April 2020) - Wang, Xiao; Tu, Haixia; Wang, Yong
Abstract : Purpose . To compare the short-term visual outcomes and intraocular optical performance of a rotationally asymmetric multifocal intraocular lens (MIOL) (SBL-3, Lenstec, Inc., Christ Church, Barbados) and an apodized diffractive MIOL (the Acrysof IQ ResTOR SN6AD1, Alcon Laboratories, Inc., Fort Worth, Texas, United States). Methods . A prospective, comparative, nonrandomized, and single-center study. Sixty-eight age-related cataract patients (81 eyes) after phacoemulsification cataract surgery and in-the-bag MIOL implantation were enrolled. Thirty-eight eyes received SBL-3, and 43 eyes received SN6AD1. Ophthalmological evaluation included uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA), corrected distance visual acuity (CDVA), modulation transfer function (MTF), Strehl ratio (SR), intraocular aberrations (4 mm optical zone), and defocus curve at 3 months postoperatively. The Chinese version of the visual function index-14 (VF-12-CN) and spectacle independence were assessed in all patients. Results . There was no statistically significant difference between groups in postoperative UDVA (p = 0.186 ). Postoperative UIVA and UNVA were significantly better for the SBL-3 group than for the SN6AD1 group (p < 0.01 ). Statistically significant differences were revealed in defocus levels from –3.50 D to −4.00 D with better visual acuities for the SBL-3 group (p < 0.01 ). For intraocular optical quality outcomes, statistically significant differences between groups were observed in RMS of intraocular total aberrations, coma, and trefoil high-order aberrations, presenting significantly higher values of these parameters in the eyes of the SBL-3 group (p < 0.01). Statistically significant differences were revealed in the MTF values at spatial frequencies of 5 and 10 cycles/degree between groups. There were no significant differences in scores of VF-12-CN, and spectacle independence between the groups (p > 0.05 ). Conclusions . Both MIOLs were able to successfully restore visual function after cataract surgery. SBL-3 provided better UIVA and UNVA with a wider range of intermediate vision.